Hardball - Paretsky, Sara (Paretsky, Sara. V.I. Warshawski novel., 2009)
When V. I. Warshawski is asked to find a man who's been missing for four decades, a search that she figured would be futile becomes lethal. Afraid to learn that her adored father might have been a bent cop working for the Chicago P.D., V. I. takes the investigation all the way to its frightening end.